2008
DOI: 10.2174/1874-470210801010068
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Antibiotics

Abstract: There is growing evidence that certain antibiotics exert their beneficial effects not only by killing or inhibiting the growth of bacterial pathogens but also indirectly by immunomodulation. This review aims at giving an overview of the immunomodulatory properties of antibiotics in different diseases: The antiinflammatory properties of macrolides in chronic inflammatory pulmonary disorders were recognized more than 15 years ago and have been well documented in the last decade. Recent data suggest that several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Broad-spectrum antibiotics are known to have a wide-ranging impact on the gut microbiome 35 and immunomodulatory effects on both the innate and adaptive components of the immune system 19 36 . Both the GI flora and the local GI immune response have the potential to prevent or limit GI colonization by C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…Broad-spectrum antibiotics are known to have a wide-ranging impact on the gut microbiome 35 and immunomodulatory effects on both the innate and adaptive components of the immune system 19 36 . Both the GI flora and the local GI immune response have the potential to prevent or limit GI colonization by C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the antibacterial properties of antibiotics and their use in the management of bacterial infections, these drugs can have an immunomodulatory effect on the properties of immune cells such as neutrophils [172,173]. In this regard, a study showed that azithromycin and chloramphenicol affect respiratory burst, apoptosis, degranulation of neutrophils as well as NET formation.…”
Section: Advantages and Disadvantages Of Netosis Inhibitionmentioning
confidence: 99%